Liberia : Second Review of Performance Under the Staff-Monitored Program and New Program for 2007. (IMF Staff Country Reports; Country Report, 2007)
This paper discusses key findings of the Second Review Under the Staff Monitored Program (SMP) and New Program for 2007 for Liberia. Performance under the SMP in the quarter to end-September was mixed. The authorities achieved all but one of the quantitative benchmarks, but they needed more time to achieve key structural benchmarks, including the review of contracts and concessions and finalization of the domestic debt and anticorruption strategies. Most of these outstanding benchmarks have now been met.